Care disruptions among patients with lung cancer: A COVID-19 and cancer outcomes study. (October 2021) - Bhalla, Sheena; Bakouny, Ziad; Schmidt, Andrew L.; Labaki, Chris; Steinharter, John A.; Tremblay, Douglas A.; Awad, Mark M.; Kessler, Alaina J.; Haddad, Robert I.; Evans, Michelle; Busser, Fiona; Wotman, Michael; et al.
Highlights: Patients with lung cancer faced significant cancer care disruptions due to COVID-19. Patients with lung cancer were at greater risk for pandemic-related care disruption. Providers must balance risks of COVID-19 versus risks of delaying cancer care. Efforts to ensure continuity of cancer care during the pandemic are warranted. Abstract: Introduction: Patients with lung cancer (LC) are susceptible to severe outcomes from COVID-19. This study evaluated disruption to care of patients with LC during the COVID-19 pandemic. Methods: The COVID-19 and Cancer Outcomes Study (CCOS) is a prospective cohort study comprised of patients with a current or past history of hematological or solid malignancies with outpatient visits between March 2 and March 6, 2020, at two academic cancer centers in the Northeastern United States (US). Data was collected for the three months prior to the index week (baseline period) and the following three months (pandemic period). Results: 313 of 2365 patients had LC, 1578 had other solid tumors, and 474 had hematological malignancies. Patients with LC were not at increased risk of COVID-19 diagnosis compared to patients with other solid or hematological malignancies. When comparing data from the pandemic period to the baseline period, patients with LC were more likely to have a decrease in in-person visits compared to patients with other solid tumors (aOR 1.94; 95% CI, 1.46–2.58), but without an increase in telehealth visits (aOR 1.13; 95% CI 0.85–1.50). Patients with LC were more likely to experience pandemic-related treatment delays than patients with other solid tumors (aOR 1.80; 95% CI 1.13–2.80) and were more likely to experience imaging/diagnostic procedure delays than patients with other solid tumors (aOR 2.59; 95% CI, 1.46–4.47) and hematological malignancies (aOR 2.01; 95% CI, 1.02–3.93). Among patients on systemic therapy, patients with LC were also at increased risk for decreased in-person visits and increased treatment delays compared to those with other solid tumors. Discussion: Patients with LC experienced increased cancer care disruption compared to patients with other malignancies during the early phase of the COVID-19 pandemic. Focused efforts to ensure continuity of care for this patient population are warranted.